Clinical Judgment When Using Coagulation Tests during Direct Oral Anticoagulant Treatment: A Concise Review - Di Minno, Alessandro; Spadarella, Gaia; Prisco, Domenico; Franchini, Massimo; Lupoli, Roberta; Di Minno, Matteo Nicola Dario (Seminars in Thrombosis and Hemostasis, 2013)
Because their anticoagulant effect is dose predictable, steady, and little influenced by diet and drugs, laboratory monitoring was deemed unnecessary in trials on venous and arterial thromboprophylaxis with the direct oral anticoagulant drugs (DOACs) rivaroxaban, apixaban, edoxaban, or dabigatran. However, there are special clinical settings in which measurement of their anticoagulant effect may be clinically desired. Because of lack of standardization between reagents employed and their global nature, the activated partial thromboplastin time (APTT) and the prothrombin time (PT) are not generally suitable for accurately assessing the anticoagulant effect of DOACs. The modified (diluted) PT reliably quantifies the anticoagulant effect of rivaroxaban or of apixaban. However, a higher intraindividual variability from one PT reagent to another is found when the data are compared with those obtained with standard PT. The HEMOCLOT (HYPHEN BioMed, France) assay is a modified (diluted) thrombin time (TT) provided with dabigatran calibrators. However, it is performed only in few specialized centers. Anti-factor Xa (anti-FXa) chromogenic assays employ routine automated coagulometers or manual spectrometers, and kits for anti-FIIa assays that measure dabigatran levels and kits for anti-Xa with rivaroxaban calibrators are commercially available. However, no correlation has been identified between any of these tests and clinical outcomes in patients taking any of the DOACs. Thus, currently, there are evidence gaps regarding the role of laboratory testing for surveillance and management of adverse events associated with DOACs. In view of this, in addition to standardization, validation of such assays is mandatory before they can be used to make clinical decisions.
Keywords: direct oral anticoagulants; ex vivo laboratory tests; patient awareness; communication/cooperation between patients and doctors